• 2022-06-01
    设f和g都是从整数集合到整数集合的映射,f(x)=2x+3, g(x)=3x+2,则[img=27x23]18031a67108ec2c.png[/img]为从整数集合到整数集合的映射,[img=116x25]18031a6719762ef.png[/img]。
  • 内容

    • 0

      设 f(x)=1-2x,g(f(x))=(1-x)/x ,则 [img=51x43]180349caea51829.png[/img] A: 0 B: 1 C: 2 D: 3

    • 1

      设 f(x)=1-2x,g(f(x))=(1-x)/x ,则 [img=51x43]180311a45a4ae1d.png[/img] A: 0 B: 1 C: 2 D: 3

    • 2

      对于给定非负整数[img=11x14]17de86c7a4e3414.png[/img],计算[img=132x24]17de86c7b1aebe2.png[/img]的方法是 A: [x^2 | x - [1..n]] B: sum[x^2 | x - [1..n]] C: sum [x | x^2 - [1..n]] D: sum [x | x - [1..n^2]] E: sum [y | y- [1..n], y = x^2] F: sum [ x*y | (x,y) - zip [1..n] [1..n]] G: sum [ x*x | (x,x) - zip [1..n] [1..n]]

    • 3

      对于给定非负整数[img=11x14]1803c4615c4a826.png[/img],计算[img=132x24]1803c461653d41a.png[/img]的方法是 A: [x^2 | x - [1..n]] B: sum[x^2 | x - [1..n]] C: sum [x | x^2 - [1..n]] D: sum [x | x - [1..n^2]] E: sum [y | y- [1..n], y = x^2] F: sum [ x*y | (x,y) - zip [1..n] [1..n]] G: sum [ x*x | (x,x) - zip [1..n] [1..n]]

    • 4

      设A到B的映射f:x→y=(x-1)2,若集合A={0,1,2},则集合B不可能是(  )